A review on medicinal plants used for treating ototoxicity and acoustic trauma induced hearing loss - Mohammad-Reza Mahm; SomayehHashemi Sheikhshabani; Farzaneh Sadat Mirfakhar; Samira Asgharzade (Universidade de São Paulo, 2019)
Hearing loss induced by chemotherapy and acoustic trauma is mainly associated with two factors, free radical formation and apoptosis pathway activation. Despite numerous efforts on reducing the effects of these factors, no definite strategy is still determined to interfere with and control these processes. In recent studies, various protective agents, including antioxidants have been used on animal models, to inhibit the formation of free radicals thus improving hearing loss.In this review article we will discuss the role of traditional herbal medicine in treatment of noise/drug induced hearing loss, focusing on medicinal plants' active substances,as well as their mechanisms of action in reducing or preventing the formation of free radicals thus increasing the rate of survival of cochlea cells. Data have been gathered since year 2000, from scientific publications including the following keywords: deafness, drug toxicity, acute trauma, medicinal herbs and oxidative stress. The study includes all herbs and medicinal plants that have been experimentally used in studies on animal models and clinical trials. The results from these studies indicate the effectiveness of most of these herbs and their active substances through their antioxidative properties. Medicinal plants reported in this review can thus be considered as effective remedies intreating noise/drug induced hearing loss,yet further studies need to be done.